Perlindungan Hukum terhadap Talent Creator atas Wanprestasi dalam Perjanjian dengan Agency Manajement - Fery, Fristy Celestia Modesty; Yuniawaty , Yenny (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
In the digital era, the profession of talent creators has become a key element in digital marketing. Agreements between talent creators and management agencies form the foundation of professional relationships to promote products or services. Breaches of contract by management agencies, such as failure to provide jobs (work opportunities) or delays in paying commissions, cause losses to talent creators both financially and in terms of reputation. Therefore, legal protection for talent creators against breaches in agreements with management agencies is necessary. This research employs a normative juridical method with a descriptive-analytical approach, which describes legal facts based on secondary data including primary legal materials such as the Civil Code (KUHPerdata) and Law Number 11 of 2008 concerning Electronic Information and Transactions (UU ITE), secondary legal materials in the form of literature and scientific journals, as well as tertiary legal materials such as legal dictionaries. In this research, the author uses a statutory approach to examine the provisions of contract law, and a conceptual approach to explore legal theories and doctrines in building an analytical framework. The research results indicate that breaches by management agencies, such as failure to provide jobs (work opportunities) and delays in paying commissions, cause losses to talent creators; therefore, talent creators can file claims for compensation against management agencies based on breaches as regulated in Article 1243 of the Civil Code (KUHPerdata). Legal protection is supported by Law Number 11 of 2008 concerning Electronic Information and Transactions (UU ITE), which recognizes the validity of digital evidence, enabling dispute resolution through mediation, arbitration, or litigation. This research recommends the preparation of detailed written agreements, due diligence on agencies, and the utilization of digital evidence to strengthen the legal position of talent creators, as well as the development of regulations to enhance transparency and accountability in the talent creator marketing industry in Indonesia.